Great minds of the Eastern intellectual tradition - Hardy, Grant, 1961-; Teaching Company (Chantilly, VA : Teaching Co., 2011)
"[This series] is an epic, comprehensive survey of the East's most influential philosphers and thinkers. In 36 lectures, [the student will be introduced to] the men and women responsible for molding Asian philosophy and for giving birth to a wide variety of spiritual and ideological systems, including Hinduism, Daoism, Confucianism, Sufism, and Buddhism."--Www.thegreatcourses.com.
Disc 6: Lecture 31 : Mohandas Gandhi: Satyagraha, or soul-force -- Lecture 32 : Fukuzawa Yukichi and Han Yongun -- Lecture 33 : Kang Youwei and Hu Shi -- Lecture 34 : Sun Yat-sen and Mao Zedong -- Lecture 35 : Modern legacies -- Lecture 36 : East and West.
DVD ; NTSC.
Thirty six lectures at 30 min. each.
Keywords: Philosophy, Asian; Philosophers; Intellectual life -- History; Philosophy -- History; Philosophy and civilization; Buddhism -- History; Hinduism -- History; Sufism -- History; Confucianism -- History; Taoism -- History; Philosophy, Indic -- History; Buddhist philosophers; Hindu philosophers; Jaina philosophers; Muslim philosophers; Philosophy -- Miscellanea; Civilization, Oriental; Filmed lectures; Educational films; Nonfiction films